Surgical site infection and its risk factors in colon surgeries - Suzimar de Fátima Benato Fusco; Natiara Medolago Massarico; Maria Virginia Martins Faria Fadul Alves; Carlos Magno Castelo Branco Fortaleza; Érika Cibele Pereira Pavan; Valéria de Castilho Palhares; Carlos Eduardo de Melo; Marla Andréia Garcia de Avila; Maria José Trevizani Nitsche (SciELO, 2016)
Abstract OBJECTIVE To identify the occurrence of surgical site infection (SSI) and its risk factors in patients undergoing colon surgery in a tertiary hospital located in the countryside of the state of São Paulo. METHOD Retrospective cohort study, with collection of information contained in the medical records of patients undergoing colon surgery in the period between January 2010 and December 2013. The studied variables were the possible risk factors related to the patient, to demographic characteristics and the surgical procedure. RESULTS In total, were evaluated 155 patients with an overall SSI incidence of 16.7%. A statistically significant association was found both in the univariate as in the multivariate analysis between the SSI and the following variables: male gender, Charlson index and mechanical bowel preparation. CONCLUSION The understanding of health professionals about the factors that influence the incidence of SSI in colon surgery may contribute to the quality of care provided to surgical patients, from effective actions to minimize the risk of infections.